Requisitos de informação para o agir público: um estudo à luz do plano nacional de logística e transportes - Lima, Alessandra Morgado Ramiro de (2011)
This study is centered in the information requirements for the elaboration of policies. The Brazilian transport sector has been chosen as locus of such problem, due to the importance of this sector as supplier of an infrastructure capable of boosting the country s development. This paper shows how the value given to information determines the choice of the decision making process model, with regard to the National Plan Logistics and Transportation (NPLT), elaborated from December 2005 to April 2007. In the above case, it has been conducted by a strategy of network articulation, made possible by the performance of several agents and their competence, in different spheres both public and private enabling a full constitution of an informational structure for the elaboration of the NPLT.